2013
DOI: 10.1007/s12291-013-0376-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of Iron Overload with Oxidative Stress, Hepatic Damage and Dyslipidemia in Transfusion-Dependent β-Thalassemia/HbE Patients

Abstract: Blood transfusion can be a life-saving therapy for β-thalassemia major and β-thalassemia/HbE (β-TM) patients with chronic anemia, major caused severe iron overload particularly in β-TM patients received only blood transfusion therapy. We aim to evaluate the association of iron overload with oxidative stress, liver damage, and elevated very low density lipoprotein cholesterol (VLDL-C) in transfusion-dependent β-TM patients. Serum ferritin, malondialdehyde (MDA), liver profiles, triglycerides levels, and VLDL-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 27 publications
3
42
0
1
Order By: Relevance
“…12,13 In thalassemia, iron mediated ROS formation, originating from imbalanced globin production and regular blood transfusions, can cause systemic tissue damage. 7,14 Antioxidant status can be investigated individually by direct measurement inside the RBC of cytoprotective enzymes such as superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px). [15][16][17][18] In our experiments, we chose to measure TAC in plasma, as some studies suggest that assessing total plasmatic antioxidant capacity is more useful than measuring antioxidant individually, since their synergistic interactions could be determined.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In thalassemia, iron mediated ROS formation, originating from imbalanced globin production and regular blood transfusions, can cause systemic tissue damage. 7,14 Antioxidant status can be investigated individually by direct measurement inside the RBC of cytoprotective enzymes such as superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px). [15][16][17][18] In our experiments, we chose to measure TAC in plasma, as some studies suggest that assessing total plasmatic antioxidant capacity is more useful than measuring antioxidant individually, since their synergistic interactions could be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Results reported by Gavin et al and Shengjiang Guan et al indicated dysfunction of heart and kidney in iron overload (2,33). In the current study, after injection of iron dextran, kidney histological damage was observed, yet treatJundishapur J Nat Pharm Prod.…”
mentioning
confidence: 39%
“…Serum iron concentration, liver biomarkers, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), and creatinine phosphokinase (CPK) 2 Jundishapur J Nat Pharm Prod. In Press(In Press):e65028.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
See 2 more Smart Citations